Patient-reported outcome measures for acne: a mixed-methods validation study (acne PROMs). Issue 3 (19th March 2021) - Hornsey, Samantha; Stuart, Beth; Muller, Ingrid; Layton, Alison M; Morrison, Leanne; King, Jamie; Thomas, Karen; Little, Paul; Santer, Miriam
Abstract : Objectives: To examine the acceptability and validity of two patient-reported outcome measures (PROMs) for adult acne, comparing them to the validated Acne-specific Quality of Life (Acne-QoL) measure. Design: Mixed-methods validation study. Setting: Participants were recruited by (1) mail-out through primary care if they had ever consulted for acne and received a prescription for acne treatment within the last 6 months, (2) opportunistically in secondary care and (3) poster advertisement in community venues. Participants: 221 (204 quantitative and 17 qualitative) participants with acne, aged 18–50 years. Outcome measures: Quantitative sub-study participants completed Acne-QoL, Skindex-16 and Comprehensive Acne Quality of Life Scale (CompAQ) at baseline, 24 hours and 6 weeks. Qualitative sub-study participants took part in cognitive think-aloud interviews, while completing the same measures. Transcribed audio recordings were analysed using inductive thematic analysis. Results: Quantitative analyses suggested high internal consistency (Cronbach's alpha 0.74–0.96) and reliability (intraclass correlation coefficient values 0.88–0.97) for both questionnaires. Both scales showed floor effects on some subdomains. Skindex-16 and CompAQ showed good evidence of construct validity when compared with Acne-QoL with Spearman's correlation coefficients 0.54–0.81, and good repeatability over 24 hours. Qualitative data uncovered wide-ranging views regarding usability and acceptability. Interviewees held strong but differing views about layout, question/response wording, redundant/similar questions and guidance notes. Similarly, interviewees differed in perceptions of acceptability of the different scales, particularly on relatability of questions and emotive reactions to scales. Conclusions: All PROMs performed well in statistical analyses. No PROM showed superior usability and acceptability in the qualitative study. Any PROM should be acceptable for further research in adult acne but researchers should consider the different domains and whether they will measure only facial or facial and trunk acne before making a selection. A new PROM or further evaluation of novel PROMs may be beneficial.